Attitudes of English as a Foreign Language Teachers and Future Teachers toward Inclusive Education: Unveiling the Certification Paradox - Luh Diah Surya Adnyani; Nyoman Sugihartini; Luh Mertasari; Nyoman Karina Wedhanti (Jurnal Pendidikan Progresif, 2026)
Teachers' attitudes are among the most significant factors that contribute to the effectiveness of inclusive education practices. Previous studies on attitudes toward inclusive education have not thoroughly examined the three primary components, including gender, age, training, and teaching experience of Indonesian English as a foreign language (EFL) teachers and future teachers, as well as certification of in-service teachers. Therefore, an investigation of the attitudes of EFL teachers and future teachers becomes paramount. The purpose of this study was to examine attitudes, actions, and processes, as well as the factors influencing attitudes toward inclusive education. Using convenience sampling, 147 EFL teachers and future teachers were recruited. This cross-sectional survey design involved online distribution of validated scales during the 2025 academic semester, with informed consent and ethical approval from institutional review boards. Participants completed the Multidimensional Attitudes toward Inclusive Education Scale (MATIES; including cognitive, affective, and behavioral components) and the second dimension of Accessibility, Process, Permanent, and Demanded Training (APTD; focusing on process) scale. The data were analyzed descriptively and using t-tests, one-way ANOVAs, and multiple regression analyses. The attitudes of EFL teachers and future teachers towards inclusive education are generally positive. There is a significant difference between those teachers. Future teachers and young in-service teachers tend to have the most positive attitude toward inclusive education. In addition, there are no statistically significant differences in gender, teaching experience with students with special needs, or training/seminar/course participation. Certified teachers tend to have less positive attitudes, which reflects the certification paradox. Indonesian EFL teachers and future teachers have positive attitudes toward inclusive education. An intensive training program and evaluation of the certification program are recommended to foster the implementation of inclusive education.Keywords: attitudes, inclusive education, EFL teachers, future teachers, certification paradox.